Production and excretion of cloacin DF13 by Escherichia coli harboring plasmid CloDF13. - Van Tiel-Menkvled, G J (1979)
The production and the mechanism of excretion of cloacin DF13 were investigated in noninduced and mitomycin C-induced cell cultures. A mitomycin C concentration was selected which did not cause lysis of cloacinogenic cells, but at the same time induced a maximal production of cloacin DF13. Native cloacin DF13, possessing killing activity, was first released into the cytoplasm. Shortly thereafter, the bacteriocin was transported through the cytoplasmic membrane and accumulated in the periplasm. Finally, cloacin DF13 was excreted into the culture medium. A small amount of cloacin DF13 remained associated with the cell surface. Producing cells did not become permeable for the cytoplasmic enzyme beta-galactosidase. Apparently the cloacin DF13 leaves the producing cells by an excretion process which is not similar to the mechanism proposed for bacterial secretory proteins. The processes of excretion by producing cells and of uptake by susceptible cells were also not identical because mutant cloacin DF13, which was not transported through the outer membrane into susceptible cells, was excreted like the wild-type cloacin DF13. The composition of the culture medium greatly affected production of cloacin DF13. The presence of sugars known to cause catabolite repression not only inhibited the production but also strongly reduced the excretion of cloacin DF13 into the culture medium.